INFERÊNCIAS EVOLUTIVAS PARA DUAS ESPÉCIES DO GÊNERO Omophoita (COLEOPTERA, CHRYSOMELIDAE): DIFERENCIAÇÃO CARIOTÍPICA E MOLECULAR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2014)
Alticinae presents karyotypic characteristics very interesting as the variation of the diploid number, sex determination system and meiotic irregularities. The most frequent chromosome number is 11 or 12 pairs. The species cytogenetically studied Oedionychina have 2n = 22,10 II + X + Y with giant sex chromosomes. In relation to the systematic position there are many divergence between the studies and problems of identification of species belonging to several genera. The study with more refined techniques and rDNA 5s mapping is recent in Coleoptera , and the few Alticinae species studied show the presence of two or three autosomal pairs. Thus, this study aims to analyze cytogenetically and propose strategies for the species karyotype differentiation of Omophoita communis and Omophoita sexnotata. Cytogenetic analysis of individuals of both populations of O. communis showed the existence of a large variation in diploid number and chromosome morphology, being possible to separate them into two cytotypes. Cytotype I presented 2n = 22 and cytotype II 2n = 12, this variation is described for the first time in the genus. Additionally, the study of the morphology of the aedeagus showed differences, indicating a likely pattern of differentiation of the two species. The phylogenetic reconstruction consensus tree analysis also presented that cytotypes show different groupings and reinforce the hypothesis of two species. The 5S rDNA gene mapping of O. sexnotata showed the presence of this cluster in all autosomes, this dispersal pattern was never described in Coleoptera before. In the literature, the dispersion of ribosomal genes is always associated with the presence of transposable elements. The sequencing of 5S rRNA fragments obtained from each chromosome of O. sexnotata resulted in similar to 5S rRNA sequences of Drosophila melanogaster transposable element EnSpm, retropseudogene 5S and microsatellite. Additionally, analysis of the secondary structure of 5S rRNA showed that the sequences obtained are not functional compared their percentage of free energy with the percentage of the original sequence of the 5S rRNA .
Keywords: Alticinae; Morfologia do Edeago; Filogenia; DNAr 5S; diferenciação cariotipica; evolução; Alticinae; Aedeagus morphology; phylogeny; karyotype differentiation; evolution; CNPQ::CIENCIAS BIOLOGICAS